Peningkatan Kemampuan Berfikir Kritis pada Siswa terhadap Konsep Fisika Kesetimbangan Benda Tegar Menggunakan Model Discovery Learning - Lubis, Yenni Khairani; Dalimunthe, Tika Rahmadani (Gravity Journal, 2025)
The learning approach in the classroom has a significant impact on the success of the educational process, so teachers need to choose the right strategy so that students are more motivated to be involved in learning. In this way, students can participate actively and optimize their critical thinking skills, one of which is through implementing the discovery learning model. However, is the application of this model effective in improving students' critical thinking skills in class XI IPA 1 SMA N 1 Siabu? This research aims to identify an increase in students' critical thinking skills through the application of the discovery learning model. This research uses a classroom action research (PTK) approach with a combination of quantitative and qualitative methods. Quantitative methods are used to measure the impact of applying the discovery learning model on critical thinking skills on the topic of equilibrium dynamics of rigid bodies, while qualitative methods are used to outline the learning implications of this research. The research subjects were 33 students of class XI IPA 1 SMA N 1 Siabu, consisting of 19 female students and 14 male students. The success indicator is determined if 75% of the total students achieve learning completion. The research results showed that student activities in cycle I were in the quite good category, and in cycle II they increased to good category. The percentage of classical completion of students' critical thinking ability test results increased from 18.1% in the pre-cycle to 36.3% in the first cycle of the first meeting, 51.5% in the second meeting, and 78.8% in the second cycle. Thus, the application of the discovery learning model has proven to be effective in improving students' critical thinking skills in class XI IPA 1 SMA N 1 Siabu Mandailing Natal.